LARG links histamine-H1-receptor-activated Gq to Rho-GTPase-dependent signaling pathways - Pfreimer, Mariana; Wieland, Thomas (Cellular signalling, 2012)
Activation of heterotrimeric G proteins, such as G12/13 and Gq, by cell surface receptors is coupled to the regulation of numerous cellular functions controlled by activated Rho GTPases. Previous studies have implicated the Rho guanine nucleotide exchange factor (RhoGEF) leukemia-associated RhoGEF (LARG) as a regulatory protein receiving stimulatory inputs from activated Gα12/13 and Gαq. However, the molecular mechanisms of the Gαq-mediated LARG activation are not fully understood and the structural elements of LARG involved in this process have remained unclear. In the present work, the specific coupling of the histamine H1 receptor (HRH1) exogenously expressed in COS-7 cells to Gq, but not to G12/13, was used to conduct a detailed analysis of receptor- and Gαq-mediated LARG activation and to define its structural requirements. The results show that HRH1-mediated activation of the strictly Rho-dependent transcriptional activity of serum response factor requires the PDZ domain of LARG and can be mimicked by activated GαqQ209L. The functional interaction between activated Gαq and LARG requires no more than the catalytic DH-PH tandem of LARG, and is independent of PLCβ activation and distinct from the mechanisms of Gαq-mediated p63RhoGEF and PLCβ3 activation. Activated Gαq physically interacts with the relevant portions of LARG in COS-7 cells and histamine causes activation of LARG in native HeLa cells endogenously expressing HRH1, Gq, and LARG. This work is the first positive demonstration of a stimulatory effect of LARG on the ability of a strictly Gq-coupled receptor to cause activation of a Rho-GTPase-dependent signaling pathway.
Available online 10 November 2011
Gesehen am 21.11.2018